Easily measureable morpho-physiological traits as selection criteria for terminal drought tolerance in groundnut (Arachis hypogaea L.) - Abdalla, Elgailani A.; Ibrahim, Abu Elhassan S.; Abuelgasim, Elhag H. (Gezira Journal of Agricultural Science; Vol 5 No 2 (2007), 2007)
This study was conducted at El Obied Research Station Farm, North Kordofan State Sudan, with the objective of identifiying easily measurable morpho-physiolgical traits that could be used in drought tolerance breeding programs. Nine groundnut mutants together with three parents were evaluated under normal and terminal drought stress environments in 2003 and 2004 cropping seasons in a randomized complete block design with four replications. The genotypes did not differ significantly in the number of days to 75% emergence, with  a range of 6-8 days. Most of the measured traits showed higher values under normal than under stressed environments. Under stressed environment, some mutants like Barberton-B-30-3 and Barberton-B-30-4, exceeded their parents in pod yield (PY) /plant, dry matter production (DM) and leaf relative water content (LRWC), whereas they showed lower specific leaf area (SLA), canopy temperature (CT) and leaf senescence (LSENS) than their parents. CT, LRWC, LSENS and PY showed relatively medium broad-sense heritab-ility estimates under stress environment. PY was positively, significantly and genotypically correlated with DM and LRWC while significantly and negatively correlated with SLA, CT and LSENS under stress enviro-nment. Since these traits are reasonably heritable, strongly correlated with PY under stress enviroment and easily measurable under field conditions, they could be suggested as selection criteria for droguht tolerance in groundnut. The mutant Barberton-B-30-3, which produced the highest PY, DM and LRWC, under terminal drought stress, could be suggested as the best drought tolerant mutant in this study bending further testing over years and locations.